Health Risk Literacy and Consumer Behavior in Selecting Facial Whitening Serums among Pharmacy Profession Students - Siti Nurhalizah; Aejeeliyah Yousuf (Tinta Emas Publisher, 2026)
The increasing use of facial whitening serums among young adults has created a public-health concern because several brightening products may contain active ingredients that require appropriate knowledge, label verification, and risk-based use. This study examined the association between health-risk literacy regarding adverse effects and consumer behavior in selecting facial whitening serums among pharmacy profession students at the University of Muhammadiyah Malang. A quantitative observational study with a cross-sectional and pre-post educational component was conducted among 60 students selected purposively from a population of 150 students. Data were collected using an online structured questionnaire measuring knowledge of adverse effects and serum-selection behavior. Instrument validity was assessed using Pearson correlation, reliability using Cronbach’s alpha, and inferential analysis using normality testing, chi-square analysis, and paired-sample t-testing at a 95% confidence level. The instruments were valid and reliable, with Cronbach’s alpha values of 0.761 for risk-knowledge items and 0.750 for serum-selection behavior. Awareness of possible adverse effects increased from 75.0% before education to 93.4% after education. Knowledge of retinoic-acid-related fetal risk increased from 60.0% to 75.0%, while attention to ingredients unsuitable for sensitive skin increased from 90.0% to 96.7%. Chi-square analysis showed a significant association between risk knowledge and serum-selection behavior (p < 0.001), and the paired-sample t-test indicated a significant post-education improvement in the composite score (t = 20.538; df = 59; p < 0.001). These findings indicate that health-risk literacy is strongly related to safer cosmetic-selection behavior. Structured cosmetovigilance education should therefore be integrated into pharmacy training and consumer-facing cosmetic counseling.